2019
DOI: 10.1177/2380084418824262
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Evidence Pertaining to Factors That Modify Risk of Early Childhood Caries

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that: • a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
72
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 39 publications
9
72
0
9
Order By: Relevance
“…While breastfeeding has sometimes been mistaken as a risk factor for ECC in the past, it is actually protective and associated with lower odds for caries (1, 27, 66, 67). However, breastfeeding beyond 24 months of age has been reported to be associated with an increased risk for ECC (68, 69).…”
Section: Discussionmentioning
confidence: 99%
“…While breastfeeding has sometimes been mistaken as a risk factor for ECC in the past, it is actually protective and associated with lower odds for caries (1, 27, 66, 67). However, breastfeeding beyond 24 months of age has been reported to be associated with an increased risk for ECC (68, 69).…”
Section: Discussionmentioning
confidence: 99%
“…A study from the United Kingdom evaluated the types of fruits and vegetables used in 329 CCF which had the fruits and vegetables in the product name and reported that CCF contained predominantly fruits and relatively sweet vegetables [ 23 ]. This is of concern, since high sugar intakes can contribute to the risk of childhood overweight/obesity and dental caries [ 24 ]. Furthermore, exposure to sweet products during infancy can promote a preference for sweet foods [ 25 ] and poor eating habits in childhood [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies confirmed that up to 24 months breastfeeding did not affected oral health, but others showed less association between breastfeeding longer than 24 months of age and risk for ECC (55).…”
Section: Evidence Opposing a Link Between Ecc And Breastfeedingmentioning
confidence: 99%